Ferroptosis-Associated Molecular Features to Aid Patient Clinical Prognosis and Therapy Across Human Cancers - Cui, Kaisa; Gong, Liang; Wang, Kang; Wang, Yuanben; Huang, Liuying; Liu, Bingxin; Li, Qilin; Zhang, Qiang; Fei, Bojian; Huang, Zhaohui (Frontiers in Immunology, 2022)
Ferroptosis is a new non-apoptotic form to regulate cell death that is mainly dependent on iron-mediated oxidative damage and subsequent cell membrane damage. Ferroptosis may be the potential therapeutic strategy for immunotherapy, chemotherapy and radiotherapy in human cancers. Numerous studies have analyzed ferroptosis-correlated signatures or genes, but a systematic landscape of associations among tumor ferroptosis, clinical outcomes, tumor microenvironment and therapies in human cancers is lacking. Here, we developed a relative ferroptosis level (RFL) combined with drive/suppress regulators and validated in Gene Expression Omnibus datasets of ferroptotic drug treatment. Based on this effective evaluation method, we classify about 7000 tumor samples into high and low RFL groups in each cancer type and observed that high RFL cases demonstrate favorable survival outcomes in nine cancer types from The Cancer Genome Atlas. Then, several RFL-correlated candidate genes that have not been reported to be ferroptosis-related were selected and were experimental validated in five cancer cell lines using Erastin treatment. We further show that both immunostimulatory and immunosuppressive phenotypes were observed in high RFL tumors, suggesting that the consideration of ferroptosis could be a potential strategy in cancer immunotherapy. Moreover, we found high RFL cases/cells showed responder or sensitivity to chemotherapy and radiotherapy. Our study provides a comprehensive molecular-level understanding of ferroptosis and may have practical implications for clinical cancer therapies, including immunotherapy, chemotherapy and radiotherapy.